How can Just War Theory help us assess a notion of legitimacy applied to the actions of non-state actors in conflict situations? - Mbuya, Nkulu Joelle (My University, 2015)
The formulation of International Law has been greatly driven by Western principles. These principles have been applied to the world at large as a result of the continuing hegemony of the global north. Consequently, what is deemed to be just and unjust, legitimate and illegitimate in international relations is dictated by these set standards that have been reified throughout history. Sovereign states, as realist theorist tend to emphasize, are at the core of international relations. One of the basic premises of Realism is that the absence of central authority in the international system is bound to lead to conflict. Various international relations theorists have contributed to this literature in their attempts to unpack causes, solutions and justifications for war. The United Nations Charter provides perhaps the most concrete guidelines and codifications of proper state conduct in the pursuit of peace and order and the resolution of conflicts. However, with the progression of history, the nature of conflict in international relations has experienced various changes. One of these changes worth analysing is the shift away from states as single most important actors in a conflict-prone international context. As a matter of fact, the recent history of international relations has been marked by the rise of non-state actors. This research paper seeks to investigate this shift by revisiting Just War Theory against non-state actors in conflict in Africa using the cases of the Mai Mai Bakata Katanga in the Democratic Republic of Congo and the Pirates in Somlia’s Gulf of Aden.
Department of International Relations School of Social Sciences
Keywords: Peace-building; International cooperation; Just war doctrine; Non-state actors (International relations)